2010
DOI: 10.1016/j.transproceed.2010.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The Prognosis of Noncutaneous, Nonlymphomatous Malignancy After Heart Transplantation: Data From the Spanish Post-Heart Transplant Tumour Registry

Abstract: Mortality among HT patients with post-HT NCNL solid organ cancers was highest for cancers of the liver or lung (79%-85% at 5 years), and lowest for prostate cancer (23%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 7 publications
0
14
0
1
Order By: Relevance
“…Sex plays a strong role, with men having greater risk of developing NMSC than women. [22][23][24]27,32,33 Longer post-transplantation follow-up time is also correlated with NMSC development. [22][23][24]27,32,33 Longer post-transplantation follow-up time is also correlated with NMSC development.…”
Section: Incidence and Risk Factors Of Skin Cancers In Otrsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sex plays a strong role, with men having greater risk of developing NMSC than women. [22][23][24]27,32,33 Longer post-transplantation follow-up time is also correlated with NMSC development. [22][23][24]27,32,33 Longer post-transplantation follow-up time is also correlated with NMSC development.…”
Section: Incidence and Risk Factors Of Skin Cancers In Otrsmentioning
confidence: 99%
“…Longer duration of immunosuppression correlates with greater number of SCCs. 24,32 The presence of premalignant infections such as human papillomavirus (HPV) and post-transplant viral warts 23 are risk factors for NMSC in the setting of chronic immunosuppression. 32,35 Two studies found that induction therapy with OKT3 and anti-thymocyte globulin therapy increased the incidence of NMSC.…”
Section: Incidence and Risk Factors Of Skin Cancers In Otrsmentioning
confidence: 99%
See 3 more Smart Citations